Standard model : from fundamental symmetries to experimental tests - Grossman, Yuval; Nir, Yosef (Oxford: Princeton University Press, 2023)
"Most of the data that is relevant for particle physics came from collider experiments. The task of particle physicists is to identify the patterns in this raw data, and to organize them in such a way that the principles that explain this variety emerge. The currently accepted theory of organization in particle physics is called the Standard Model (SM), which describes three of the four known fundamental forces and establishes principles of symmetry amongst particles. This book describes the SM as it is understood today, providing readers with a deep understanding of the symmetry principles at play in constructing models of particle physics. It is designed to be used as a textbook, accompanying a one semester course for graduate students. While generally presented as an optional elective, graduate-level courses on particle physics are common to most universities that offer a PhD in Physics. While there are variety of textbook offerings in the space, including our own Elementary Particle Physics in a Nutshell and The Standard Model in a Nutshell, this book is unique in its systematic and pedagogical approach, as well as for its inclusion of cosmological tests, which current texts lack. It also has a unique focus on model-building. Many of the other books on this topic attempt to cover a mix of QFT and the SM. This text focuses squarely on the Standard Model and does not attempt to concurrently teach QFT. Rather, it assumes some prior knowledge (while not requiring mastery of the subject). Lastly, the book will offer a greater number of homework-level practice problems than its counterparts"--
"An authoritative, hands-on introduction to the foundational theory and experimental tests of particle physicsThe Standard Model is an elegant and extremely successful theory that formulates the laws of fundamental interactions among elementary particles. This incisive textbook introduces students to the physics of the Standard Model while providing an essential overview of modern particle physics, with a unique emphasis on symmetry principles as the starting point for constructing models. The Standard Model equips students with an in-depth understanding of this impressively predictive theory and an appreciation of its beauty, and prepares them to interpret future experimental results.Describes symmetry principles of growing complexity, including Abelian symmetries and their application in QED, the theory of electromagnetic interactions, non-Abelian symmetries and their application in QCD, the theory of strong interactions, and spontaneously broken symmetries and their application in the theory of weak interactionsDerives the Lagrangian that implements these symmetry principles and extracts the phenomenology that follows from it, such as elementary particles and accidental symmetriesExplains how the Standard Model has been experimentally tested, emphasizing electroweak precision measurements, flavor-changing neutral current processes, neutrino oscillations, and cosmologyDemonstrates how to extend the model to address experimental and observational puzzles, such as neutrino masses, dark matter, and the baryon asymmetry of the universeFeatures a wealth of problems drawing from the latest researchIdeal for a one-semester graduate course and an invaluable resource for practitionersOnline solutions manual (available only to instructors)"--
Includes bibliographical references (pages 305-307) and index.
Keywords: Standard model (Nuclear physics); SCIENCE / Physics / General; SCIENCE / Physics / Nuclear